Phrasemosemiosis as a Process of Linguacreative Thinking (Proceedings of Southern Federal University. Philology, 2017)
Nikolay F. Alefirenko  (Belgorod State National Research University,Belgorod, Russian Federation)The  article deals with the problems of idiom production and interpretation,  related to the  presign forms emergence of information accumulation and storage, contained in cognitive-based derivation of idiom building. The author puts forward the idea that the presign stage of the semiosis  process and  idiom understanding  is a  cognitive model that precedes  not only the formation of the idiom semantic structure  but  also its understanding. The fact that the cognitive model of phraseosemiosis is the diagram of  discursive meaning embodiment  and  discourse itself is the form of its indirectly derivative existence stipulates  the necessity to show how the cognitive-discoursive mechanisms of  idiom  building are connected with presign forms  of  sense accumulation and storage.It is suggested that the elements of the representational code, situated in the cognitive depth of the right semisphere layers of discoursive cognition keep information which has to be coded tby means ofidioms. These very layers form the part  of  conceptual sphere which is constructed by special  cognitive structures which produce idioms. The author calls them discoursive-modus concepts. A mental syntactic model of a discoursive-modus concept  which projects the syntagmatic outline of the designator of the idiom-sign is created with the direct involvement of the right  semisphere. The character of this designator is determined by the “special syntax” of the inner speech that produces sketchy, fragmentary, abbreviated structures. This conclusion is especially important for the explanation of idiom building because much in the structures of the designator and the designatum  of  already  produced idioms stays implicit, not formally expressed.Since  senses of words participating in idiom building are more dynamic and wider than their meanings some illogical mechanisms of their uniting and blending with each other are sometimes revealed. They give the opportunity “to bring to a common denominator” even such  associative-metaphorical relations of semes  in the structure of the phraseological meaning which are difficult for perception.Key words:  presign, representational code, mental model, inner form, sign,  gestalt, idiom phraseme.DOI 10.23683/1995-0640-2017-2-50-73